Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1159/000338572
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Synthesising Data in a Network of Registries for Systemic Psoriasis Therapies

Abstract: Background: Large disease registries are the preferred method to assess long-term treatment safety. If psoriasis registries collaborate in a network, their power to assess safety is increased. Objective: To identify heterogeneity in psoriasis registries and methodological challenges for synthesising the data they provide. Methods: We surveyed the registries in PSONET and identified and addressed the challenges to collaborative analysis for the network in several round table meetings. Results: Eight out of 10 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 28 publications
(15 reference statements)
2
46
1
2
Order By: Relevance
“…In our study, psoriasis was the most common (55%) underlying etiology of pre-existing dermatosis, which was much higher than all the previous reports. As a result, we concluded that there might be a higher frequency of psoriasis or a greater tendency for its generalization in our district [10]; furthermore, unlike in western reports [11], injudicious use of medications, either by the individual or prescribed by physicians, may partly be responsible for the higher rate of psoriasis (the most frequently suspected trigger factors were upper respiratory tract infections and withdrawal of oral medicines including systemic corticosteroids or Chinese traditional herbal medicines). In our study, we also found bullous pemphigoid, hypereosinophilic syndrome and dermatomyositis as causes of erythroderma, which have never or rarely been mentioned in previous reports.…”
Section: Discussionmentioning
confidence: 56%
“…In our study, psoriasis was the most common (55%) underlying etiology of pre-existing dermatosis, which was much higher than all the previous reports. As a result, we concluded that there might be a higher frequency of psoriasis or a greater tendency for its generalization in our district [10]; furthermore, unlike in western reports [11], injudicious use of medications, either by the individual or prescribed by physicians, may partly be responsible for the higher rate of psoriasis (the most frequently suspected trigger factors were upper respiratory tract infections and withdrawal of oral medicines including systemic corticosteroids or Chinese traditional herbal medicines). In our study, we also found bullous pemphigoid, hypereosinophilic syndrome and dermatomyositis as causes of erythroderma, which have never or rarely been mentioned in previous reports.…”
Section: Discussionmentioning
confidence: 56%
“…Cut-off PASI value ≥10 [10] PASI score was assessed independently by 2 physicians after attending a PASI training course [3]. In case of discordance, the 2 investigators reviewed the scores together with a third physician Who failed to respond to Patients were clinically evaluated at monthly intervals, and they underwent the necessary laboratory and instrumental tests at baseline and at recommended intervals [10].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the same registries showed wide differences in the rates of patients treated with the biologics [3][4][5][6]. A possible explanation is that the European Medicines Agency (EMA) did not describe in detail the eligibility criteria for biologics and systemic conventional therapies [7][8][9][10], and therefore they left a margin of discretion in their interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The registries agreed on the Psonet protocol and a common set of variables and procedures; recent work has focused on understanding heterogeneity in patient populations. 17 The IRHLT (described previously) is another example of a registry that uses the network model. This registry incorporates data from 16 national-level transplantation registries as well as data submitted directly from 80 institutions.…”
Section: Multi-national Registry Modelsmentioning
confidence: 99%